THE «4К» FORMULA IN ACTION: SKILLS FORMATION TECHNOLOGIES OF THE XXI CENTURY - Bondar, N.P.; Tatarchuk, T.V.; Kalinina, T.V.; Cheshenko, Y.D. (SWorld-Ger Conference proceedings, 2024)
These theses consider the perspective of introducing "4K" technology into the educational process. The development of such skills and abilities as creativity, critical thinking, sociability, and the ability to work in a team among students is very importa